2005
DOI: 10.1111/j.1365-2141.2005.05454.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant somatic hypermutation and expression of activation‐induced cytidine deaminase mRNA in mediastinal large B‐cell lymphoma

Abstract: SummaryTo determine the possible role of aberrant somatic hypermutation (ASHM) and activation-induced cytidine deaminase (AID) expression in the pathogenesis of mediastinal large B-cell lymphoma (MBL), the mutational status of genes affected by ASHM, including c-MYC, PAX-5 and RhoH, was analysed, and the expression level of AID mRNA in tumour specimens from six patients with MBL was determined. Mutations in one or more genes and high expression of AID mRNA were detected in all the six cases of MBL. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…3 However, this seems to be restricted to cases with a high FLT3-LM/WT ratio. 4 In the present case only a low ratio…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…3 However, this seems to be restricted to cases with a high FLT3-LM/WT ratio. 4 In the present case only a low ratio…”
mentioning
confidence: 92%
“…3 The involvement of aberrant SHM in PMLBCL has been suggested by a recent report based on a limited number of cases. 4 These observations prompted our comprehensive analysis aimed at exploring the involvement of aberrant SHM of PIM-1, PAX-5, RhoH/TTF and c-MYC in a sizeable panel of PMLBCL and at comparing the mutational spectrum with that of systemic DLBCL.…”
mentioning
confidence: 99%
“…In fact, despite some overlapping features, [37][38][39][40][41] NLPHL and cHL represent distinct diseases that clearly differ from DLBCL in terms of biologic properties, morphologic appearance, clinical course, and response to therapy. 1,42 The most probable explanation is that genetic alterations in addition to aberrant SHM may eventually concur in the pathogenesis of HL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the expression of AID in different lymphoma types using reverse transcriptase-polymerase chain reaction technology, western blot, and recently, also immunohistochemistry, examining cell lines and tissue samples of lymph nodes. [15][16][17][18][19][20][21] In the present study, we investigated the expression of AID in bone marrow infiltrates in different types of malignant lymphomas. A set of bone marrow trephines with infiltration of Hodgkin lymphoma (HL) and nonHodgkin lymphomas (NHL) of B cell and T-cell type was selected and the expression of AID was assessed immunohistochemically.…”
mentioning
confidence: 99%